Highly toughened poly(lactic acid) blends prepared by reactive blending with a renewable poly(ether‐block‐amide) elastomer. Issue 13 (21st October 2020) - Xia, Yiwei; Wang, Guangxin; Feng, Yulin; Hu, Yuexin; Zhao, Guiyan; Jiang, Wei
Abstract: Renewable poly(ether‐block‐amide) (PEBA) elastomer was grafted with glycidyl methacrylate (GMA) to prepare PEBA‐GMA, then it was melting blended with poly (lactic acid) (PLA) in an effort to achieve fully bio‐based super‐toughened PLA materials. The notched Izod impact strength of PLA/PEBA‐GMA blend was significantly enhanced when the content of PEBA‐GMA was higher than 20 wt%, and the tensile toughness was also improved. It was found a new copolymer was formed at the interface due to the reaction of the end groups (OH, COOH) of PLA with the epoxide group of PEBA‐GMA. This greatly improves the interfacial adhesion between PLA and PEBA‐GMA component, leading to finer dispersed particles of PEBA‐GMA which were better wetted by the PLA matrix. Therefore, the highly enhanced notched impact strength was ascribed to the effective reactive compatibilization promoted by the interfacial reaction. This provides a new idea for preparing super tough PLA materials with bio‐based elastomer, which will widely extend the application of PLA. Abstract : Comparing with PLA/PEBA blend, the interfacial reactive compatibilization of PLA/PEBA‐GMA was dramatically enhanced by the functionalization of PEBA with GMA, leading to better wetting of the dispersed phase by the PLA matrix.